Arsenic (III, V), indium (III), and gallium (III) toxicity to zebrafish embryos using a high-throughput multi-endpoint in vivo developmental and behavioral assay. (April 2016) - Olivares, Christopher I.; Field, Jim A.; Simonich, Michael; Tanguay, Robert L.; Sierra-Alvarez, Reyes
Abstract: Gallium arsenide (GaAs), indium gallium arsenide (InGaAs) and other III/V materials are finding increasing application in microelectronic components. The rising demand for III/V-based products is leading to increasing generation of effluents containing ionic species of gallium, indium, and arsenic. The ecotoxicological hazard potential of these streams is unknown. While the toxicology of arsenic is comprehensive, much less is known about the effects of In(III) and Ga(III). The embryonic zebrafish was evaluated for mortality, developmental abnormalities, and photomotor response (PMR) behavior changes associated with exposure to As(III), As(V), Ga(III), and In(III). The As(III) lowest observable effect level (LOEL) for mortality was 500 μM at 24 and 120 h post fertilization (hpf). As(V) exposure was associated with significant mortality at 63 μM. The Ga(III)-citrate LOEL was 113 μM at 24 and 120 hpf. There was no association of significant mortality over the tested range of In(III)-citrate (56–900 μM) or sodium citrate (213–3400 μM) exposures. Only As(V) resulted in significant developmental abnormalities with LOEL of 500 μM. Removal of the chorion prior to As(III) and As(V) exposure was associated with increased incidence of mortality and developmental abnormality suggesting that the chorion may normally attenuate mass uptake of these metals by the embryo. Finally, As(III), As(V), and In(III) caused PMR hypoactivity (49–69% of control PMR) at 900–1000 μM. Overall, our results represent the first characterization of multidimensional toxicity effects of III/V ions in zebrafish embryos helping to fill a significant knowledge gap, particularly in Ga(III) and In(III) toxicology. Graphical abstract: Highlights: As(III), As(V), Ga(III) caused significant but moderate mortality (500–1000 μM). Only As(V) caused developmental abnormalities (LOEL 500 μM). Zebrafish embryo dechorionation increased endpoint incidence for As(III) and As(V). As(III), As(V), In (III) (0.9–1 mM) significantly reduced photomotor response activity.